2020
DOI: 10.1186/s12879-020-05124-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of virological failure, genetic diversity and drug resistance among people living with HIV in a minority area in China: a population-based study

Abstract: Background: Liangshan Yi Autonomous Prefecture is one of the areas that most severely affected by human immunodeficiency virus (HIV) in China, and virological failure on antiretroviral therapy (ART) is serious in this area. Analyses of prevalence and determinants of ART failure, the genetic diversity and drug resistance among people living with HIV (PLWH) helps improve HIV treatment efficiency and prevent HIV transmission. Methods: A total of 5157 PLWH were recruited from 2016 to 2017. The venous blood samples… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
0
18
1
Order By: Relevance
“…Previous studies had shown that regions for relatively severe HIV-1 transmission dynamics might be due to human mobility, relatively developed traffic, and strong economic activity, 30 , 31 notably, regions with high drug-resistant clustering rates of PLWH who virological failure for ART may not be matched for regions with severe epidemics in this study, it may be related to PWLH in southern Sichuan was mainly of age ≥50, as ART virological failure usually occurs the elderly people. 14 , 19 As the worst-hit HIV epidemic region in China, 14 Liangshan had a low drug resistance phylogenetic clustering rate (7.54%), which may be attributed to poor traffic and economic activity. Besides, China’s 13th five-year-plan has achieved huge effect for PLWH in Liangshan, 32 to a certain extent, inhibited the spread of HIV, thus affecting the DR phylogenetic clustering rate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies had shown that regions for relatively severe HIV-1 transmission dynamics might be due to human mobility, relatively developed traffic, and strong economic activity, 30 , 31 notably, regions with high drug-resistant clustering rates of PLWH who virological failure for ART may not be matched for regions with severe epidemics in this study, it may be related to PWLH in southern Sichuan was mainly of age ≥50, as ART virological failure usually occurs the elderly people. 14 , 19 As the worst-hit HIV epidemic region in China, 14 Liangshan had a low drug resistance phylogenetic clustering rate (7.54%), which may be attributed to poor traffic and economic activity. Besides, China’s 13th five-year-plan has achieved huge effect for PLWH in Liangshan, 32 to a certain extent, inhibited the spread of HIV, thus affecting the DR phylogenetic clustering rate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that young men, especially MSM, and some subtypes (eg, CRF55_01B, CRF01_AE) may have a higher transmission risk. 10,11 In addition, reports showed that some demographic differences and HIV-related behaviors (eg, gender differences, ART adherence and ART regimens) lead to the risk of drug resistance with virological failure among PLWH, which were reported among PLWH in some countries, such as China, [12][13][14] Uganda, 15 Malawi, 16 Cameroon. 17 Yuan had reported that DR transmission in MSM with virological failure was concentrated in urban cities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the low prevalence of virologic failure in our cohort could be explained in that almost one half of participants were government officers having obtained high education level and stable life activities resulting in good adherence to their ART. 9 , 30 …”
Section: Discussionmentioning
confidence: 99%